CCL21/CCR7 enhances the proliferation, migration, and invasion of human bladder cancer T24 cells. - Miao Mo; Mi Zhou; Lu Wang; Lin Qi; Kehua Zhou; Long-Fei Liu; Zhi Chen; Xiong-Bing Zu (PLoS ONE, 2015)
To investigate the effects of CCL21/CCR7 on the proliferation, migration, and invasion of T24 cells and the possible associated mechanisms: expression of MMP-2 and MMP-9, and regulation of BCL-2 and BAX proteins.T24 cells received corresponding treatments including vehicle control, antibody (20 ng/mL CCR7 antibody and 50 ng/ml CCL21), and 50, 100, and 200 ng/ml CCL21. Proliferation was evaluated by MTT assay; cell migration and invasion were assayed using a transwell chamber. Cell apoptosis was induced by Adriamycin (ADM). The rate of cell apoptosis was examined by flow cytometry using annexin V-FITC/PI staining. Western-blot was used to analyze MMP-2 and MMP-9 and BCL-2 and BAX proteins.CCL21 promoted T24 cell proliferation in concentration-dependent manner with that 200 ng/mL induced the largest amount of proliferation. Significant differences of cell migration were found between CCL21treatment groups and the control group in both the migration and invasion studies (P < 0.001 for all). The expressions of MMP-2 and MMP-9 proteins were significantly increased after CCL21 treatment (p < 0.05 for all). Protein expression of Bcl-21 follows an ascending trend while the expression of Bax follows a descending trend as the concentration of CCL21 increases. No difference was found between the control group and antibody group for all assessments.CCL21/CCR7 promoted T24 cell proliferation and enhanced its migration and invasion via the increased expression of MMP-2 and MMP-9. CCL21/CCR7 had antiapoptotic activities on T24 cells via regulation of Bcl-2 and Bax proteins. CCL21/CCR7 may promote bladder cancer development and metastasis.